The perceptions of deaf youth about HIV/AIDS at two schools for the deaf in the Eastern Cape Province. - Nonkelela, Lumka (My University, 2015)
It is evident from research studies that deaf youth in South Africa have limited knowledge or, rather, are misinformed about issues related to HIV/AIDS (Barnett & Whiteside, 2002). This is not a pure South African problem as Heuttel and Rothstein (2001) note those international studies on differences in HIV/AIDS knowledge between deaf and hearing youth indicates that deaf youth do not have the necessary knowledge about HIV/AIDS. To address this problem the South African government made a commitment to render and strengthen effective HIV/AIDS education to deaf learners (The White Paper 6 on Inclusive Education, 2001). Therefore, this study was aimed at exploring deaf youth’s perceptions about HIV/AIDS, the impact of HIV/AIDS, as well as the role that deaf youth play in the fight against HIV/AIDS in schools. A qualitative research approach was used for this study and a convenience sample of forty participants from two schools for the deaf in the Eastern Cape Province was used. The sample comprised twenty learners from each school, ranging from 14-21 years of age. Interviews were used as a data collection tool. The study has four findings, that is: deaf youth do not have critical knowledge about HIV/AIDS; deaf youth access information through conversations (with peers) and television; life skills teachers put more emphasis on religious education than talking explicitly about HIV/AIDS and discussions about HIV/AIDS are seldom held for fear of stigmatisation and due to various perceptions about HIV transmission. The study concludes that it is imperative for deaf youth to have the right knowledge and skills to reduce their vulnerability to HIV/AIDS therefore; this dissertation recommends that there is a need to address issues related to knowledge improvement, access to information and the social stigma against HIV/AIDS. The study further notes that there is a need to research, reasons why HIV/AIDS is not incorporated in all learning areas; other factors that may be causing teachers not to be able to offer in-depth HIV/AIDS education to deaf youth and to determine the extent to which SLED materials are being put to use by teachers of deaf learners.
Keywords: Deaf youth; Deafness; HIV/AIDS and perceptions